Image of the Civil war in Lebanon Homless Novel for Jobor Al Doweihi - Bakri, Ahlam Mazen (Journal of Arabic Language Sciences and Literature, 2022)
The research highlighted on the image of the civil war in Lebanon, through Jabour Douaihy's novel (Homelessness), so he examined it in an objective study that showed the image of the civil war in Lebanon, to present a picture of Lebanon before and during the outbreak of the war, and a structural study to look at the harmony of the artistic construction represented by different narratives techniques such as characters, time, place, narrator, and thematic construction.
Keywords: civil war; homelessness; war